Bioremediation of nitrogen‐containing organic pollutants using phenol‐stimulated activated sludge: performance and microbial community analysis. Issue 11 (28th May 2018) - Zhang, Xuwang; Qu, Yuanyuan; You, Shengnan; Ma, Qiao; Zhou, Hao; Zhang, Lizhi; Zhang, Lihang; Jing, Jiawei; Liu, Lifen
Abstract: BACKGROUND: Coking wastewater generally contains high levels of phenolics and nitrogen‐containing organic pollutants, thus seeking an appropriate wastewater treatment strategy is necessary. In this study, the triplicate phenol‐stimulated activated sludges (group C) were constructed for aerobic treatment of nitrogen‐containing organic pollutants (indole, pyridine and quinoline), and glucose‐stimulated sludges (group B) were used as control. RESULTS: Both groups maintained high efficiency (>90%) for removal of nitrogen‐containing organic pollutants after long‐term operation (90 days). Illumina MiSeq sequencing of 16S rRNA gene amplicons revealed that alpha diversity decreased after receiving nitrogen‐containing pollutants. Glucose exerted protective effects on sludge microbes, but phenol‐stimulated microbial consortia showed greater stability when without supplementation of stimulated substrates. Canonical correspondence analysis and Mantel tests indicated that the microbial community structure was significantly associated with indole and quinoline ( P  < 0.05). Among the dominant genera, Comamonas was the core genus in both groups for pollutants removal, while Thauera and Sphingomonas should be key functional taxa in glucose‐stimulated sludges, with Pseudoxanthomonas, Brevundimonas and Shinella in phenol‐stimulated sludges. PICRUSt (Phylogenetic Investigation of Communities by Reconstruction of Unobserved States) analysis suggested that the important functional metabolic capabilities should be those related to Cytochrome P450 enzymes and naphthalene degradation, which were significantly correlated with the nitrogen‐containing organic pollutants ( P  < 0.05). CONCLUSION: The results indicated that phenol‐stimulated microbial consortia could be used for efficient removal of nitrogen‐containing organic pollutants, and therefore could have potential for the bioremediation of coking wastewater. © 2018 Society of Chemical Industry